Malaysia : Firm Competitiveness, Investment Climate and Growth - World Bank (Washington, DC, 2012)
The objective of this report is to explore firm competitiveness, the investment climate, and growth in Malaysia. This report is structured as follows. The first two chapters provide an assessment of the investment climate. The last two chapters examine how productivity enhancing programs, skills and technology, have performed in Malaysia. The diagnosis is based on the survey data as well as on cross-country comparisons. Chapter 1 reports on the investment climate and firm performance in the manufacturing sector. Chapter 2 presents the findings on the investment climate and firm performance in the services sector. Chapter 3 examines skills performance and the contribution of training and education to skills performance. Chapter 4 provides a diagnosis of the technological capability of firms. This report also identifies areas that require further work including carrying out a detailed assessment of key elements of the regulatory environment; and undertaking a larger firm level survey to achieve a better assessment of the services sector as a source of growth.